Global exponential stability of positive periodic solutions for a cholera model with saturated treatment - Quan, Hongzheng; Zhou, Xueyong; Liu, Jianzhou (Nonlinear Analysis: Modelling and Control, 2019)
In this paper, we consider a cholera model with periodic incidence rate and saturated treatment function. Under certain conditions, we establish a criterion on the global exponential stability of positive periodic solutions for this model by using a novel method. We illustrate our theoretical results with numerical simulations by using Matlab.
Keywords: cholera model; global exponential stability; periodic incidence rate; positive periodic solution